Oral Monomethyl Fumarate Therapy Ameliorates Retinopathy in a Humanized Mouse Model of Sickle Cell Disease - Promsote, Wanwisa (Antioxid Redox Signal, 2016)
Aims: Sickle retinopathy (SR) is a major cause of blindness in sickle cell disease (SCD). The genetic mutation responsible for SCD is known, however; oxidative stress and inflammation also figure prominently in the development and progression of pathology. Development of therapies for SR is hampered by the lack of (a) animal models that accurately recapitulate human SR and (b) strategies for noninvasive yet effective retinal drug delivery. This study addressed both issues by validating the Townes humanized SCD mouse as a model of SR and demonstrating the efficacy of oral administration of the antioxidant fumaric acid ester monomethyl fumarate (MMF) in the disease. Results: In vivo ophthalmic imaging, electroretinography, and postmortem histological RNA and protein analyses were used to monitor retinal health and function in normal (HbAA) and sickle (HbSS) hemoglobin-producing mice over a one-year period and in additional HbAA and HbSS mice treated with MMF (15 mg/ml) for 5 months. Functional and morphological abnormalities and molecular hallmarks of oxidative stress/inflammation were evident early in HbSS retinas and increased in number and severity with age. Treatment with MMF, a known inducer of Nrf2, induced γ-globin expression and fetal hemoglobin production, improved hematological profiles, and ameliorated SR-related pathology. Innovation and Conclusion: United States Food and Drug Administration-approved formulations in which MMF is the primary bioactive ingredient are currently available to treat multiple sclerosis; such drugs may be effective for treatment of ocular and systemic complications of SCD, and given the pleiotropic effects, other nonsickle-related diseases in which oxidative stress, inflammation, and retinal vascular pathology figure prominently. Antioxid. Redox Signal. 25, 921–935.